2017
DOI: 10.5901/jesr.2017.v7n1p173
|View full text |Cite
|
Sign up to set email alerts
|

Factors which Influence Students Enterpreneurship Intentions: The Role of Education Programs, Subjective Norms and Perceived Behavioral Control

Abstract: The entrepreneur aim is a very important factor, which is considered as a key element in youth employment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…This means that there is a direct influence between PBC and EI. The results of this study are in line with previous research conducted by Anggadwita & Dhewanto (2015), Apasieva (2020), Cera & Furxhiu (2017), Handayani & Prajogo (2020), Sahinidis et al (2019), andShabbir (2016).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This means that there is a direct influence between PBC and EI. The results of this study are in line with previous research conducted by Anggadwita & Dhewanto (2015), Apasieva (2020), Cera & Furxhiu (2017), Handayani & Prajogo (2020), Sahinidis et al (2019), andShabbir (2016).…”
Section: Resultssupporting
confidence: 92%
“…Tuu (2015) The research results found an influence between perceived behavioral control and consumers' intention in a coastal province in Central Vietnam. Cera & Furxhiu (2017) The study results found a statistically significant influence of PBC on entrepreneurial intention.…”
Section: Introductionmentioning
confidence: 77%
“…This finding contradicts the findings of Iqbal et al (2012); Liñán et al (2011); Matlay, Othman, Hashim, and Ab Wahid (2012). However, it confirms the finding of Cera and Furxhiu (2017). Furthermore, this study also finds that entrepreneurial education, which is observed from teacher's competence, learning material, and learning method used in the learning process, is not able to form entrepreneurial readiness, which is seen from the ownership of social capital, mental capital, and knowledge capital.…”
Section: Discussionsupporting
confidence: 82%
“…The study recorded a negative and insignificant relationship between the desire to be independent and entrepreneurial orientation. Cera and Nevila (2018) carried out a study on factors which influence students" entrepreneurship intention: the role of education programs, subjective norms and perceived behavioural control. The study was carried out to observe whether there is a positive relationship between entrepreneurial purpose and the three independent variables hypothesized as influential.…”
Section: Empirical Reviewsmentioning
confidence: 99%